LLMs in Practice: Results from a Survey with Software Development Professionals in Brazil - Tolio, Antônio Sergio; Becker, Enzo Zanini; Bagesteiro, Felipe Colpo; Tolfo, Cristiano; Fontoura, Lisandra Manzoni (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: The emergence of Large Language Models (LLMs) has been transforming the development of information systems, directly impacting activities across the system life cycle. Understanding how these technologies affect work practices is essential for advancing the Information Systems (IS) field and for guiding their adoption by organizations. Scientific and/or Practical Problem: Despite the growing use of LLMs in information systems development, there is still limited knowledge on how professionals across different roles, levels of experience, and work modalities perceive the impact of generative AI on daily activities, decision-making, and team performance. Proposed Solution and/or Analysis: This study investigates the perceptions and experiences of Brazilian software developers regarding the integration of Generative AI (LLMs) into their professional practice. The analysis aims to identify which activities are most impacted by AI, the most frequently adopted tools, and the level of trust professionals place in AI-generated outputs. Related IS Theory: The study aligns with the Systemic and Socially Aware Perspective for Information Systems challenge of GranDSI-BR, by examining how emerging technologies reshape sociotechnical systems and the dynamics of professional work. Research Method: An online survey was conducted with 94 professionals in the field of information systems development, covering diverse profiles. Data were collected through customized Likert scales, multiple-choice checkboxes, and closed-ended questions. Summary of Results: Findings highlight that, although the adoption of LLMs significantly increases developers’ productivity, there is still a moderate level of trust in the outputs and the absence of consolidated governance policies. Contributions and Impact to IS area: The results provide both theoretical and practical insights into the adoption of generative AI in information systems development, offering valuable guidance for researchers, managers, and educators seeking to integrate these technologies into IS safely and ethically.